Plant biotechnology Proceeding of lectures - Yutaka, Hirita (CTU/JICA, 2001)
This is a lucture for plant biotechnology of Mr. Yutaka Hirita. The lecture describes the biotechnology in plant improvement from the "Agricultural revolution at 10.000 years ago" to the Japanese biotechnology in 16th - 18th century".